A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters - de Araújo, Marcel Santos; Bichuette, Maria Elina; Bauchan, Gary R.; Ochoa, Ronald; Feres, Reinaldo José Fazzio (Zootaxa, 2018)
Neocarus coronatus n. sp., is described from caves and the surrounding epigean habitats from a karst area of São Desidério county, Bahia state, Brazil. A dissection procedure is presented for the better use of scarce Opilioacaridae material, especially to analyze gut contents. Sexual dimorphism is presented, mainly differences in the density of setae on the dorsal shield in the prominent triangular anterior region. Females have an ovipositor with 3 pairs of smooth digitiform projections and 6–8 eugenital setae. Adults have a palpal tibiotarsus with 4 d setae. Using Low-Temperature Scanning Electron Microscopy (LT-SEM), evaluation of the chaetotaxy (especially setal shape) and morphology are greatly improved over standard light microscopy techniques enhancing the interpretation of characters for species differentiation. Also, we discuss the fragility of microinvertebrates in cave habitats.